Analisis Kebijakan Zonasi: Upaya Pemerataan Pendidikan di Indonesia - Nurohman, Fajar; Goro, Siti Fatimah; Harahap, Chisa Belinda (UIN Sunan Gunung Djati Bandung, 2025)
The zoning system in Indonesia's education aims to improve access and equity through a location-based approach. This policy seeks to eliminate the stigma between